Icequake source mechanisms for studying glacial sliding - Hudson, Thomas S.; Brisbourne, Alex M.; Walter, F.; Graff, D.; White, R. S.; Smith, A. M. (Journal of Geophysical Research: Earth Surface, 2019)
Improving our understanding of glacial sliding is crucial for constraining basal drag in ice dynamics models. We use icequakes, sudden releases of seismic energy as the ice slides over the bed, to provide geophysical observations that can be used to aid understanding of the physics of glacial sliding and constrain ice dynamics models. These icequakes are located at the bed of an alpine glacier in Switzerland and the Rutford Ice Stream, West Antarctica, two extremes of glacial settings and spatial scales. We investigate a number of possible icequake source mechanisms by performing full waveform inversions to constrain the fundamental physics and stress release during an icequake stick-slip event. Results show that double-couple mechanisms best describe the source for the events from both glacial settings and the icequakes originate at or very near the ice-bed interface. We also present an exploratory method for attempting to measure the till shear modulus, if indirect reflected icequake radiation is observed. The results of this study increase our understanding of how icequakes are associated with basal drag while also providing the foundation for a method of remotely measuring bed shear strength